Wood plastic composite from Senduduk / Mohd Afiq Mohtar, Nur Syuhada Mohd Saidi and Wan Azlin Wan Ibrahim - Mohtar, Mohd Afiq; Mohd Saidi, Nur Syuhada; Wan Ibrahim, Wan Azlin (2008)
This is a study of producing wood plastic composite ot thermoplastic composite from Senduduk (Melastoma malabathricum). Wood plastic composite from Senduduk followed from the size of particle geometry consists 250µm 150µm, 75µm and fines, filler loadings consists 5%,10%,and 15%, and amount of MAPP consists 0%,1.5%,and 3.0%. Test such as tensile, bending, and water absorption are carried out to determine either wood Senduduk is suitable as filler in making of wood plastic composite. The result showed that particle geometry 250µm is the strongest than 150µm, 75µm, and fines. While for the filler loadings, the result indicates that the board which contains more plastics is the strongest which means filler loadings 5% was the highest. Therefore, for MAPP, the strongest is MAPP 3.0% while the weakest is no MAPP at all. In generally, using 250µm size of particle, filler loadings 5% and MAPP 3.0% that all the sources from Senduduk is the most suitable quantity for being mixing with polypropylene to make wood plastic composite.